Low-dose estradiol and endothelial and inflammatory biomarkers in menopausal overweight/obese women. (3rd July 2016) - da Silva, L. H. A.; Panazzolo, D. G.; Marques, M. Ferreira; Souza, M. G. C.; Paredes, B. Dias; Nogueira Neto, J. F.; Leão, L. M. C. S. M.; Morandi, V.; Bouskela, E.; Kraemer-Aguiar, L. G.
Abstract: Objective: We aimed to investigate the effects of low-dose transdermal estrogen on endothelial and inflammatory biomarkers in menopausal overweight/obese women. Methods: We recruited 44 menopausal women (47–55 years; body mass index 27.5–34.9 kg/m 2 ) and divided them into estradiol (1 mg/day; n  = 22) or placebo groups ( n  = 22). They were double-blinded, followed and treated for 3 months. At baseline and post-intervention, inflammatory biomarkers (hs-CRP, IL-1β, IL-6, MCP-1 and TNF-α) and of vascular injury (activated circulating endothelial cells, CEC-a) and repair (endothelial progenitor cells, EPC) were quantified. Resting CECs (CEC-r) were also assessed. Microvascular reactivity and vasomotion were analyzed by laser-Doppler flowmetry. Results: Volunteers (51.8 ± 2.3 years; mean body mass index 31.5 ± 2.5 kg/m 2 ) had been menopausal for 3 (range 2–5) years. After treatment, no changes were observed in the placebo group, while levels of CEC-r and EPC increased in the estradiol group. In this group, no changes in inflammatory biomarkers were observed but it required a lower cumulative dose of acetylcholine to achieve peak velocity during endothelial-dependent vasodilatation and there was increased endothelial-independent vasodilatation. Conclusions: The short-term use of low-dose transdermal estradiol therapy in overweight/obese menopausal women increased markers of vascular repair and improved microvascular reactivity without changing the inflammatory biomarkers. Clinical trial registration: NCT01295892 atwww.clinicaltrials.gov .